Miss Peregrine's home for peculiar children : the graphic novel - Riggs, Ransom (Riggs, Ransom. Novel of Miss Peregrine's Peculiar Children., 2013)
"A horrific family tragedy sets sixteen-year-old Jacob on a journey to a remote island off the coast of Wales, where he discovers the crumbling ruins of Miss Peregrine's Home for Peculiar Children. As Jacob explores its abandoned bedrooms and hallways, it becomes clear that the children were more than just peculiar. They may have been dangerous. They may have been quarantined on a deserted island for good reason. And somehow--impossible though it seems--they may still be alive"--Publisher's website.